Essays on the economics and management of pet food - Hobbs, Lonnie, Jr. (Kansas State University, 2023)
Pet food is an important component of the fast-growing global pet care industry, driven by increasing pet ownership and changing customer preferences. This dissertation contains three essays designed to provide research-based insights on the economics and management of pet food aimed at informing future research, product development, and marketing strategies in pet food. The objectives of the first essay are to identify the most relevant research gaps and research insight needed to inform raw materials, production, and marketing and distribution decisions in pet food industry. The methods include analysis of primary data from a survey of 76 pet food decision makers and systematic review of academic and non-academic literature. The second essay is aimed at examining factors that contribute to the presence of overweight or obesity in pets and related implications for pet food manufacturers. The methods involve analysis of primary data on feeding and exercise practices from a survey of 1,173 dog owners. The third and final essay is aimed at improving the understanding of pet food demand. Specifically, it utilizes a Generalized Exact Affine Stone Index (GEASI) model applied to panel data on 75,936 pet food buyers in 46 U.S. markets to test for the presence of pre-committed demand within pet food demand structure. Collectively these essays provide a range of new insights targeted at (i) informing future research in pet food economics and management, (ii) informing pet food industry strategies for developing and sustaining competitive advantage, and (iii) informing policy makers and industry stakeholders on how pet food customers respond to price changes.
Keywords: Pet food; Agribusiness; Research needs; Pet obesity; Demand